High Precision 3D Printed Syringe Pump for Contact Angle Goniometer - Vito Sentosa; Riski Titian Ginting; Fadhillah Azmi; Despaleri Despaleri Perangin-Angin (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2021)
Contact angle goniometer is a tool used to measure the contact angle of a surface which is usually coated with nanomaterial. Contact angle goniometer has an important part, that is syringe pump as a tool for dripping a number of liquids with high precision and accurate flowrate. The function of the syringe pump is to control amount and feedrate of  liquid on a milliliter to microliter scale per minute using a simple microcontroller. In this study, this syringe pump used an arduino as a controller  and a stepper motor as a syringe driver. Casing and the syringe pump mechanism were designed with AutoCAD Fusion360 software and printed using a 3D printer. This syringe pump has an accuracy value of 99.5%, a precision value of 99.7% and a deviation value 0.4 µL which is based on the solution measured using Mettler Toledo 204 analytical balance. From the result, it is obtained that the syringe pump has been used for the contact angle goniometer with an experiment of water being dripped onto the ABS plastic surface with flowrate 100 µL/minute and the surface contact angle was analyzed using imageJ software and the result of the contact angle was 179°. Therefore, based on the result of this study, it can be concluded that the syringe pump can be used as a contact angle goniometer